BUDIDAYA IKAN AIR TAWAR DI KELURAHAN BORONG KECAMATAN TANRALILI KABUPATEN MAROS SULAWESI SELATAN - Beddu Tang; Darmawati; Muhammad Nur; Jayadi; Harlina (LP2M Universitas Hasanuddin, 2024)
The aquaculture sector has now made a real contribution to food security both in terms of increasing production, and consumption of animal protein, providing employment opportunities, increasing income, and regional development. Tanralili District has an area of ​​around 89.45 km and a population of 31,488 people, which is quite promising for developing the freshwater fisheries sector because it has water sources. Borong Village has an area of ​​4.49 km² and a population of 1,704 people with a population density of 379.51 people/km² in 2017. Borong Village, Tanralili District, Maros Regency is one of the areas that has the potential for freshwater fisheries, especially fish cultivation. freshwater. From the results of the visit to the fish cultivator group in the Borong sub-district, the service team formulated and set the objectives of this activity, namely increasing the knowledge and skills of partners in managing and developing freshwater fish cultivation businesses, increasing knowledge and skills in the business of making fish feed and knowing the procedures making accountable business reports. This community service method uses the Participatory Rural Appraisal (PRA) method which focuses on community activity and involvement as the main subject accompanied by a team. This method is carried out through counseling and training for partners to increase partners' knowledge and skills in managing tilapia cultivation businesses. The success of the community service program can be seen from the results of the pre-test and post-test from the knowledge and skills aspects based on the activities that have been carried out and increased by 75%, so this program can be said to be running as expected. — Sektor perikanan budidaya kini telah memberikan kontribusi nyata dalam ketahanan pangan baik dari segi peningkatan produksi, konsumsi protein hewani, penyediaan lapangan kerja, peningkatan pendapatan dan pengembangan wilayah. Kecamatan Tanralili memiliki luas wilayah sekitar 89,45 Km dan jumlah penduduk sebanyak 31.488 jiwa, cukup menjanjikan untuk pengembangan sektor perikanan air tawar karena memiliki sumber air. Kelurahan Borong memiliki luas wilayah 4,49 km² dan jumlah penduduk sebanyak 1.704 jiwa dengan tingkat kepadatan penduduk sebanyak 379,51 jiwa/km² pada tahun 2017. Kelurahan Borong Kecamatan Tanralili Kabupaten Maros salah satu wilayah yang memilki potensi perikanan air tawar terutama budidaya ikan-ikan air tawar. Dari hasil kunjungan terhadap kelompok pembudidaya ikan di kelurahan Borong, maka tim pengabdi merumuskan dan menetapkan tujuan dari kegiatan ini adalah meningkatkan pengetahuan dan keterampilan mitra dalam mengelola dan mengembangkan usaha budidaya ikan air tawar, meningkatkan pengetahuan keterampilan dan keterampilan usaha pembuatan pakan ikan serta mengetahui tata cara pembuatan laporan usaha yang akuntabel. Metode pengabdian kepada masyarakat ini menggunakan metode Participatory Rural Appraisal (PRA) yang berfokus pada keaktifan dan keterlibatan masyarakat sebagai subjek utama didampingi oleh tim. Metode ini dilakukan dengan penyuluhan dan pelatihan kepada mitra untuk meningkatkan pengetahuan dan keterampilan mitra dalam mengelola usaha budidaya ikan nila. Keberhasilan program pengabdian kepada masyarakat tampak dari hasil pre-test maupun post-test dari aspek pengetahuan dan keterampilan berdasarkan kegiatan yang telah dilakukan dan meningkat sebesar 75%, sehingga dengan demikian program ini dapat dikatakan berjalan sesuai harapan.